Análise do esforço amostral para ecologia comportamental: onças pardas como exemplo - Ribeiro, Juliana Maria [UNESP] (2014)
TThe detection of large carnivores such as the Puma ( Puma concolor ) , is hindered by the fact that they show low density, elusive habits and are hard to be seen. Sampling procedures via noninvasive methods, like using feces, can allow the access to a number of information regarding the behavioral ecology of the species, including the identity of each i ndividual – using DNA extraction - home range and diet . The use of feces as an indirect population measurement in wildlife management and conservation depends on the successful collection of them . Faced with this, we analyzed th e sampling effort to collect Pumas’ feces in order to optimize time and cost in planning field actions . A nthropic and abiotic variables of the study area were analyzed: dista nces between sampling sites to ponds, farmhouse and roads; the average rainfall in the gathering period; time p eriod from the last rainfall; the period between visits and time interval from the last sample found. In all pathways there were trails of footprints from pumas , but feces were found only in specific spots. Thus, territorial marking by these animals, using chemical and physical patterns, may be due to ecological causes from the species itself , and anthropogenic and abiotic factors . This study indicat ed puma preference for locations close to ponds and those more isolated from human activity . It was also pos sible to estimate a range of days that optimizes the field visits, with the average number of days in the period between visits being 7 - 9 days as the optimal interval for field visits in the aim of finding puma feces. And it was establish ed that is most pr obable to find a sample when the last one has been found around 20 days before.